Socialization of Diarrhea Prevention in School-Age Children Using Healthy Pocket Media at Elementary School UPT 101800 Deli Tua Timur, Deli Tua District, Deli Serdang Regency - Napitupulu, Farida; Sinurat, Sofia Januarti; Tamariahna, Ezra; Simanjuntak, Veronica; Sipayung, Yunita Angelika (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Diarrhea remains a major health problem in Indonesia, especially among school-aged children, generally caused by a lack of understanding of personal hygiene and healthy eating habits. This activity aims to increase elementary school students' knowledge about diarrhea prevention through the interactive educational media